Bio-Roof material based on oil palm fibre / Julaida Kaliwon - Kaliwon, Julaida (Institute of Graduate Studies, UiTM, 2017)
Nature of roof that covers the very top of the building, has encouraged related research, especially regarding the properties, types, problems and materials for roofs. In recent years, awareness about environmental pollution and sustainability, has driven the demand for roof coverings that are more sustainable. Currently, the use of local raw materials that are easily found, in addition to reducing waste, and reuse of materials is a key features of construction materials. The use of recycled materials based on palm oil can be profitable for the farmers and consumers in general. The objective of this research is to produce an advanced composite material from oil palm empty fruit bunch (EFB) at the same time exploring the mechanical and physical properties of this material as a preparation to develop a substitute’s material for sustainable roofing material. The mechanical and physical properties of oil palm EFB as roofing material is originally tested as per American Standard (ASTM) and British Standard (BS). Materials are selected based on normal concrete mix with the addition of oil palm empty fruit bunch fibres in various batches. The oil palm empty fruit bunch (EFB) fibre is obtained from MPOB Research Centre and there is no treatment done to the selected fibre. The selected cement to sand ratio used is 1:2, with six different water to cement ratio (0.32, 0.37, 0.42, 0.47, 0.52 and 0.57). The thickness of the sample is 10mm and percentage of fibre used is 0.5%, 1.0&, 1.5% and 2.0%. Fibre sizes are divided into four categories; OS, LS, MS and SS. The sizes are range from 0.7mm -14.04mm length. The river sand is used as an aggregate with sizes ranging from 0.06 to 2mm which is passing a 2mm to 2.5 mm mesh size sieve…